Marinobacter Dominates the Bacterial Community of the Ostreococcus tauri Phycosphere in Culture - Lupette, Josselin; Lami, Raphaël; Krasovec, Marc; Grimsley, Nigel; Moreau, Hervé; Piganeau, Gwenaël; Sanchez-Ferandin, Sophie (Frontiers in Microbiology, 2016)
Microalgal-bacterial interactions are commonly found in marine environments and are well known in diatom cultures maintained in laboratory. These interactions also exert strong effects on bacterial and algal diversity in the oceans. Small green eukaryote algae of the class Mamiellophyceae (Chlorophyta) are ubiquitous and some species, such as Ostreococcus spp., are particularly important in Mediterranean coastal lagoons, and are observed as dominant species during phytoplankton blooms in open sea. Despite this, little is known about the diversity of bacteria that might facilitate or hinder O. tauri growth. We show, using rDNA 16S sequences, that the bacterial community found in O. tauri RCC4221 laboratory cultures is dominated by γ-proteobacteria from the Marinobacter genus, regardless of the growth phase of O. tauri RCC4221, the photoperiod used, or the nutrient conditions (limited in nitrogen or phosphorous) tested. Several strains of M. algicola were detected, all closely related to strains found in association with taxonomically distinct organisms, particularly with dinoflagellates and coccolithophorids. These sequences were more distantly related to M. adhaerens, M. aquaeoli and bacteria usually associated to euglenoids. This is the first time, to our knowledge, that distinct Marinobacter strains have been found to be associated with a green alga in culture.